If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -6 = 3(x + 4) Reorder the terms: -6 + 5x = 3(x + 4) Reorder the terms: -6 + 5x = 3(4 + x) -6 + 5x = (4 * 3 + x * 3) -6 + 5x = (12 + 3x) Solving -6 + 5x = 12 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -6 + 5x + -3x = 12 + 3x + -3x Combine like terms: 5x + -3x = 2x -6 + 2x = 12 + 3x + -3x Combine like terms: 3x + -3x = 0 -6 + 2x = 12 + 0 -6 + 2x = 12 Add '6' to each side of the equation. -6 + 6 + 2x = 12 + 6 Combine like terms: -6 + 6 = 0 0 + 2x = 12 + 6 2x = 12 + 6 Combine like terms: 12 + 6 = 18 2x = 18 Divide each side by '2'. x = 9 Simplifying x = 9
| -15X^5y^4/6x^4y^2 | | y=-10+2x | | -5.04/1.26 | | (x+20)3x+44=180 | | -5x+6(-4x+11)=-104 | | 8y+7x=-56 | | -5+6(-2+11)=-104 | | 10h-2=-94 | | 19/2 | | 36x^8-13x^4+1=0 | | 0.8=-1.12 | | 10+2w=68 | | 9*4x=8*4x+2 | | 6x+4=5x-13 | | X-6/3=-8 | | 4(-6x-3)=84 | | -1.19+5.3= | | -2(x+1)+3(2x-1)=2(x+2)-6 | | -16-8k=k+2 | | 2x-5(5x+11)=83 | | 660=4800*.055*t | | .2*y+1.5= | | 18*n=6 | | 10(.4+.1y)+y=4 | | .5+2y=3y-.25 | | 6.2(1.19)= | | r=660*4800*.055 | | 3x^2-4.4x+1.3=0 | | 9/4×2/3 | | cos(2*x)+cos^2(x)-sin^2(x)=1 | | r=4800*.055/660 | | -30x-3y=-12 |